Reliability study of Mahajan's classification of gingival recession: A pioneer clinical study - Ajay Mahajan; Divya Kashyap; Amit Kumar; Poonam Mahajan (Wolters Kluwer Medknow Publications, 2014)
Background: Gingival recession defects (GRD) are one of the most commonly encountered conditions for which periodontal treatment is required. Several attempts have been made to classify GRD. Among all the classifications Millers classification for gingival recessions is the most accepted. Recently, several limitations and drawbacks have been pointed out in Miller's classification system. The aim of the present study is to test the reliability of the recently proposed Mahajan's Modification of the Miller's Classification for GRD. Materials and Methods: All 15 males and 11 females between the ages of 22 and 55 years (mean age, 37.15 year) with at least one buccal gingival recession were consecutively recruited by the same periodontist in order to test the reliability of the new classification of GRD. The classification was tested by two examiners blinded to the data collected by the other examiner. Intra-rater and inter-rater agreement was assessed. Results: The new classification system of gingival recessions was tested in a total of 175 gingival recessions in 26 patients. The intraclass correlation coefficient for inter-rater agreement was 0.90, showing an almost perfect agreement between the examiners. Conclusion: The newly proposed classification system eliminates the drawbacks and limitations associated with Miller's classification system and can be used to classify GRD reliably.